MelastomaTRAITs 1.0: A database of functional traits in Melastomataceae, a large pantropical angiosperm family - Reginato, Marcelo (2024)
The recent availability of open-access repositories of functional traits has revolutionized trait-based approaches in ecology and evolution. Nevertheless, the underrepresentation of tropical regions and lineages remains a pervasive bias in plant functional trait databases, which constrains large-scale assessments of plant ecology, evolution, and biogeography. Here, we present MelastomaTRAITs 1.0, a comprehensive and updatable database of functional traits for the pantropical Melastomataceae, the ninth-largest angiosperm family with 177 genera and more than 5800 species. Melastomataceae encompass species with a wide diversity of growth forms (herbs, shrubs, trees, epiphytes, and woody climbers), habitats (including tropical forests, savannas, grasslands, and wetlands from sea level to montane areas above the treeline), ecological strategies (from pioneer, edge-adapted and invasive species to shade-tolerant understory species), geographic distribution (from microendemic to continental-wide distribution), reproductive, pollination, and seed dispersal systems. MelastomaTRAITs builds on 581 references, such as taxonomic monographs, ecological research, and unpublished data, and includes four whole-plant traits, six leaf traits, 11 flower traits, 18 fruit traits, and 27 seed traits for 2520 species distributed in 144 genera across all 21 tribes. Most data come from the Neotropics where the family is most species-rich. Miconieae (the largest tribe) contains the highest number of trait records (49.6%) and species (41.1%) records. The trait types with the most information in the database were whole-plant traits, flowers, and leaf traits. With the breadth of functional traits recorded, our database helps to fill a gap in information for tropical plants and will significantly improve our capacity for large-scale trait-based syntheses across levels of organization, plant–animal interactions, regeneration ecology, and thereby support conservation and restoration programs. There are no copyright restrictions on the dataset; please cite this data paper when reusing the data.